Neuropsychiatric Burden of SARS-CoV-2: A Review of Its Physiopathology, Underlying Mechanisms, and Management Strategies - Aliteia-Maria Pacnejer; Anca Butuca; Carmen Maximiliana Dobrea; Anca Maria Arseniu; Adina Frum; Felicia Gabriela Gligor; Rares Arseniu; Razvan Constantin Vonica; Andreea Loredana Vonica-Tincu; Cristian Oancea; Cristina Mogosan; Ioana Rada Popa Ilie; et al. (Viruses, 2024)
The COVID-19 outbreak, caused by the SARS-CoV-2 virus, was linked to significant neurological and psychiatric manifestations. This review examines the physiopathological mechanisms underlying these neuropsychiatric outcomes and discusses current management strategies. Primarily a respiratory disease, COVID-19 frequently leads to neurological issues, including cephalalgia and migraines, loss of sensory perception, cerebrovascular accidents, and neurological impairment such as encephalopathy. Lasting neuropsychological effects have also been recorded in individuals following SARS-CoV-2 infection. These include anxiety, depression, and cognitive dysfunction, suggesting a lasting impact on mental health. The neuroinvasive potential of the virus, inflammatory responses, and the role of angiotensin-converting enzyme 2 (ACE2) in neuroinflammation are critical factors in neuropsychiatric COVID-19 manifestations. In addition, the review highlights the importance of monitoring biomarkers to assess Central Nervous System (CNS) involvement. Management strategies for these neuropsychiatric conditions include supportive therapy, antiepileptic drugs, antithrombotic therapy, and psychotropic drugs, emphasizing the need for a multidisciplinary approach. Understanding the long-term neuropsychiatric implications of COVID-19 is essential for developing effective treatment protocols and improving patient outcomes.